2019
DOI: 10.1038/s41467-019-13236-9
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between α2-chimaerin and Rac1 activity determines dynamic maintenance of long-term memory

Abstract: Memory consolidation theory suggests that once memory formation has been completed, memory is maintained at a stable strength and is incapable of further enhancement. However, the current study reveals that even long after formation, contextual fear memory could be further enhanced. Such unexpected enhancement is possible because memory is dynamically maintained at an intermediate level that allows for bidirectional regulation. Here we find that both Rac1 activation and expression of α2-chimaerin are stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
(78 reference statements)
4
34
2
Order By: Relevance
“…Furthermore, it is shown that Rac1 activity mediates reversible forgetting. α2-Chimaerin, through inhibition of Rac1 activity during the maintenance stage, reverses forgetting to sustain memory (Lv et al, 2019).…”
Section: Rac1 Gtpase In Memory Forgettingmentioning
confidence: 99%
“…Furthermore, it is shown that Rac1 activity mediates reversible forgetting. α2-Chimaerin, through inhibition of Rac1 activity during the maintenance stage, reverses forgetting to sustain memory (Lv et al, 2019).…”
Section: Rac1 Gtpase In Memory Forgettingmentioning
confidence: 99%
“…SI has shown to elevate Rac1 activity in hippocampal tissue, inducing social recognition memory (SRM) forgetting and long-term potentiation (LTP) decline in mice; According to this finding, Inhibiting of Rac1 Activity Blocked Progressed Decline of LTP and suppressed forgetting of SRM in isolated adult mice. However, Rac1 activity had no influence on short-term (15-min) memory in the socially isolated period (86).…”
Section: Antidepressant Drugsmentioning
confidence: 83%
“…The results obtained from electrophysiological studies support the roles of Rho GTPases in synaptic transmission and plasticity. For example, increased Rac1 activity, either through KO/knockdown of Rac1 upstream GAP proteins such as alpha-chimaerin and BCR/ABR, or the expression of constitutively active Rac1 mutants, led to unstable theta-burst stimulation (TBS)-induced LTP that gradually decayed to the baseline response at the CA1 synapse ( Oh et al, 2010 ; Liu et al, 2016 , 2018 ; Lv et al, 2019 ). On the other hand, decreased Rac1 activity, either through the expression of dominant negative Rac1 mutants or the upstream GAP protein alpha-chimaerin, or through genetic deletion of MAP1B, resulted in more stable LTP ( Glebov et al, 2015 ; Liu et al, 2016 , 2018 ; Lv et al, 2019 ).…”
Section: Rho Gtpases In Synaptic Plasticitymentioning
confidence: 99%